Comparing traditional and constrained disturbance-observer based positional control. (March 2021) - Bélai, Igor; Huba, Mikulas; Vrancic, Damir
This paper compares three different position controllers of electrical drives equipped by binomialn th order filters, which are offering filtering properties important in a quantization noise attenuation. To demonstrate their impact, a non-filtered P-PI control is considered, as a reference. The comparative framework includes a filtered P-PI control, a filtered linear pole assignment PD controllers with a disturbance observer (DO) based integral action and its constrained modification. In terms of a total variation, depending on noise and process properties, all filtered controllers are capable to bring down the undue controller activity at the plant input from 10 to more than 100 times. Furthermore, thanks to the applied disturbance observer, the constrained control derived for a double integrator is shown to fully exploit the closed loop capabilities without any trajectory generation, taking into account the control constraints. Thus, the simplified controller design may focus on other important aspects.